IMPLEMENTASI PAJAK PENGHASILAN USAHA MIKRO KECIL DAN MENENGAH (STUDI KASUS UMKM WILAYAH SEMARANG) (Proceeding Fakultas Ekonomi, 2013)
This study aims to determine how the counting, recording, and reporting of tax made by the Micro, Small and Medium Enterprises (SMEs) in the region of Semarang as the implementation of self assessment system.Samples wereobtained from the Ministry of Cooperatives and SMEs Semarang. Sample was selected using a convenience sampling a number of 126 SMEs. While using descriptive qualitative data analysis. The results showed that the taxpayer has anunderstanding of the tax laws relating to the rate and time of payment of taxes. In fact, SMEs often have overpaid or underpaid in the taxation process. Steps to be done is to adjust our transaction overpayments or underpayments, although not in accordance with Financial Accounting Standards of Business Entities Without Public Accountability.Keywords : Self Assessment System, Income Tax, Small Medium Entrepresis (SMEs)